Does a community based nutrition project work? an evaluation of the Muktagachha pilot nutrition initiative in Bangladesh - Hyder, SM Ziauddin; Jalal, Chowdhury S B; Roy, Rita Das; Chowdhury, AMR; Yusuf, HKM (Research and Evaluation Division, Brac, 2019)
A study was undertaken to evaluate the impact of the multidisciplinary Muktagacha pilot nutrition project on the nutritional status of under-2 children, adolescent girls and pregnant and lactating mothers in three areas covered by the project - Paratongi, Gabtoli and Chcchua. Both quantitative and qualitative methods were used in the study. Quantitative data included infonnation on nutritional status of the target population. Data were taken only for January and July of the years from 1994 to 2000. Qualitative data, collected mainly through focal group discussions (FGD), included infonnation on health and nutrition status of the target population and perception at household, village and community levels about the nutrition project. Results showed that the project made partial success in achieving the target objectives.